FAKTOR-FAKTOR YANG MEMPENGARUHI PENGGUNAAN ALAT KONTRASEPSI PADA PASANGAN USIA SUBUR DI PUSKESMAS TANJUNG REJO KABUPATEN DELI SERDANG TAHUN 2020 - Diana Wulan; Edy Marjuang Purba; Rismalia Tarigan (LPPM Sekolah Tinggi Ilmu Kesehatan Siti Hajar Medan, 2021)
The Family Planning Program as a component of reproductive health aims to cultivate Happy and Prosperous Small Family Norms. The proportion of contraceptive use in Deli Serdang District has not met the target, as well as in the Tanjung Rejo Health Center working area is still lacking. This study aims to determine the factors that affect the use of contraceptives in fertile aged couples at the Tanjung Rejo Public Health Center, Deli Serdang District in 2020. This studi is an analytic observational with a cross sectional study approach. The population is all mothers of reproductive age couples who live in the working area of Tanjung Rejo Public Health Center, totaling 230 mothers. The number of samples used was 55 people obtained using simple random sampling technique. The data analysis technique used chi square. The results obtained in this study were that most respondents used contraceptives (59.3%). There is a relationship between knowledge and occupation and the use of contraceptives in women (p<0.05). There is no relationship between age, education, number of children and perceptions of the value of children with the use of contraceptives in mothers of PUS at Tanjung Rejo Health Center (p> 0.05). It is necessary to increase communication, information and education activities by health workers so that the knowledge of PUS about contraceptives is getting better